Effects of Pre-Evisceration Electrical Stimulation and Polyphosphate Marination on Color and Texture of Early Harvested Chicken Broiler Breast Fillets - Young, L.L.; Smith, D.P.; Cason, J.A.; Walker, J.M. (International Journal of Poultry Science, 2005)
Early harvested broiler breast fillets from electrically stimulated and non-stimulated carcasses were marinated in either saline or saline containing sodium tripolyphosphate to determine whether the stimulation and phosphate interact in such a way as to affect texture or color of non-aged breast fillets. Stimulated carcasses produced fillets with lower pre-marination pH (6.1 ±0.1 verses 6.5 ±0.1) and shear values (6.4 ±0.3 kg verses 15.5 ±0.3 kg) than unstimulated carcasses. Polyphosphate increased shear values of fillets from unstimulated by almost 1 kg, but not of those from stimulated carcasses. No other stimulation by polyphosphate interactions that affect texture or color of the fillets were detected.